Sketching Tomorrow’s Mediascape – And Beyond - Carroll, Mary; Remael, Aline (Journal of Audiovisual Translation, 2022)
Dear Readers, As the guest editors of this special issue of JAT, we hope that you will enjoy reading the selected articles and that they will inspire you to explore new research avenues. It has been a pleasure for us to edit this issue and to acquaint ourselves with the research presented in it. We hope that our introduction will also provide food for thought. We have always enjoyed working in audiovisual translation and media accessibility and trust that it will continue to be a thriving, expanding and creative field of practice and research. Mary Carroll and Aline Remael